The nigger of the 'Narcissus' an authoritative text, backgrounds and sources, reviews and criticism - Conrad, Joseph 1857-1924 (A Norton critical edition, 1979)
This account of the voyage of a sailing ship from Bombay harbour to the Port of London explores the psychological pressures on a group of nineteenth century seamen as they face the extemes of nature and the secrets and evasions of two of their comrades.